Everyman - Roth, Philip 1933-2018 (Houghton Mifflin, 2006)
A successful commercial artist with three very different ex-wives, a daughter who adores him, and two sons who despise him, the protagonist finds his confidence, sense of independence, and well-being undermined by an attack of illness in middle age.